Az erőszakos közösülés és a kapcsolódó bűncselekmények dogmatikai alapkérdései az 1878-1989 közötti időszakban és szabályozási előzményei - Fődi, Violett (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The legal situation of women has undergone many changes during the history; therefore, it is an extremely interesting topic and it is suitable for extensive research. The examination of said topic should be started from the entry into force of the first Hungarian penal code, the Csemegi Code (1878). The sacrament of marriage and the dignity of women received special protection in this period, since the protected legal interest of these crimes is primarily the woman’s interest, which required legal protection, to have a disposal of her sexual life. Over time, however, morals began to loosen, the social perception changed, and divorce became possible, therefore the Act V of 1961 and the Act IV of 1978 on the Criminal Code judged sexual offenses from a different perspective. In what follows, I want to focus on forced sexual intercourse and some of the crimes associated with it.